(untitled) (Libellarium: journal for research in the field of information and related sciences, 2012)
Cultural heritage institutions, archives, libraries and museums, which share the common goal of safeguarding and enabling wide accessibility to and use of cultural heritage, have developed in different but not diametrically opposing directions. Many scientists and practitioners from archival science, librarianship, museology and the wider area of information science have therefore studied, over many years, fundamental principles and characteristics of their activity and similarities and differences between these institutions and professions with the ultimate aim of discovering and describing potential models and guidelines for their coordinated action. First papers on this topic in the 20th century appeared in 1930s. Authors of these papers were most often librarians and archivists whose writing was initiated by their immediate working and professional environment. Based on the analysis and overview of accessible literature this paper presents and comments the thoughts of the author who was writing on this subject for over five decades, from 1930s to 1980s. These authors came, in most cases, from the United States of America and they dealt with similarities and differences between archives and libraries. Museum professionals joined this discussion only in 1960s by introducing specific characteristics and aspects of museums and museum work. In order to contribute to the understanding of interrelationships and evident convergence of these three cultural heritage institutions, which resulted in their mutual respect and in some cases with practical and active collaboration in particular in the modern networked society, the authors will try to present the development of theoretical and methodological thought on this phenomenon. The paper will provide a critical review of the most important authors who wrote on this topic from the first works that appeared through the last decade of the 20th century.